EXPLORING STUDENTS’ CONFIDENCE IN SPEAKING ENGLISH THROUGH GROUP DISCUSSION ACTIVITIES AT MA ASY-SYARIF SIDANG KOTO LAWEH - Amalia, Cinta; Sastri, Lena; Harisa, Elfa (JR-ELT (Journal of Research in English Language Teaching), 2025)
This study explores how group discussion activities can improve students’ confidence in speaking English at MA Asy-Syarif Sidang Koto Laweh, a pesantren-based senior high school. Many students initially struggled with anxiety, limited vocabulary, and hesitation when speaking. A descriptive qualitative method was used, involving two eleventh-grade classes. Data were collected through classroom observation, documentation, and informal interviews. The results show that group discussion significantly increased students’ willingness to speak, vocabulary recall, and overall participation. Working in small groups helped students feel more comfortable expressing ideas, receiving peer support, and practicing before presenting. Although each class showed different learning dynamics, both demonstrated positive improvement. This study concludes that group discussion is an effective strategy for enhancing students’ speaking confidence in EFL classrooms.